Sonochemical synthesis of a 2D–2D MoSe2/graphene nanohybrid electrode material for asymmetric supercapacitors. Issue 2 (20th December 2018) - Kirubasankar, Balakrishnan; Vijayan, Shobana; Angaiah, Subramania
Abstract : A sonochemical route is used to prepare a few layers of MoSe2 and its 2D–2D nanohybrid is prepared with graphene by a solvothermal process. This nanohybrid exhibits a high specific capacitance of 945 F g −1 . An ASC device MoSe2 /G‖AC is fabricated, which delivers an energy density of 26.6 W h kg −1 and a power density of 0.8 kW kg −1 . Abstract : Molybdenum selenide (MoSe2 ) nanosheets are prepared by a simple and facile sonochemical route. To optimize the synthesis process, the sonication is tested at three different time durations (15, 30 and 45 min) with a constant power of 500 W. In order to improve the electrochemical performance of the exfoliated MoSe2 nanosheets, we report the hybridization of 2D-MoSe2 with 2D-graphene by a simple solvothermal method. The exfoliated MoSe2 nanosheets are perpendicularly oriented on the surface of the graphene nanosheets. These MoSe2 nanosheet edges have a large number of electrochemically active sites, and the graphene sheets provide effective mass transportation of ions at the electrode–electrolyte interface. Cyclic voltammetry reveals the pseudocapacitive behaviour of a MoSe2 /graphene nanohybrid based electrode. From galvanostatic charge–discharge studies, the specific capacitance is found to be 945 F g −1 at a current density of 1 A g −1 . An asymmetric supercapacitor (ASC) device is fabricated, which delivers a specific capacitance of 75 F g −1 (@1 A g −1 ) with an energy density of 26.6 W h kg −1 and a power density of 0.8 kW kg −1, and it retains 88% of its capacitance even after 3000 cycles.